Carbon Fibers Embedded With Iron Selenide (Fe3Se4) as Anode for High-Performance Sodium and Potassium Ion Batteries - Mahmood, Asif; Ali, Zeeshan; Tabassum, Hassina; Akram, Aftab; Aftab, Waseem; Ali, Rashad; Khan, Muhammad Waqas; Loomba, Suraj; Alluqmani, Ahmed; Adil Riaz, Muhammad; Yousaf, Muhammad; Mahmood, Nasir (Frontiers in Chemistry, 2020)
The development of sodium and potassium ion batteries (SIBs/KIBs) have seen tremendous growth in recent years due to their promising properties as potential replacement for lithium ion batteries (LIBs). Here, we report ultrafine iron selenide (Fe3Se4) nanoparticles embedded into one-dimensional (1D) carbon fibers (Fe3Se4@CFs) as potential candidate for SIBs/KIBs. The Fe based metal-organic framework particles (MOFP) are used as Fe source to obtain high dispersion of the iron species in the product. The Fe3Se4@CF consisted of ultrafine particles of Fe3Se4 with an average particle size of ~10 nm loaded into CFs with an average diameter of 300 nm. The product exhibited excellent specific activity of ~439 mAh/g and ~435 mAh/g at current density of 50 mA/g for SIBs and KIBs, respectively. In addition, the as prepared anodes (Fe3Se4@CFs) exhibited excellent capacity retention up to several hundred cycles (700 cycles for SIBs and 300 cycles for KIBs). The high activity and excellent stability of the developed electrodes make Fe3Se4@CFs a promising electrode for next generation batteries.